Regional Currency Arrangements: Insights from Europe - Josef Christl (Oesterreichische Nationalbank (OeNB), 2006)
This paper focuses on the requirements and features of a successful monetary union on the basis of the optimum currency area theory, the "logical roadmap" for integration as proposed by Balassa as well as the economic and institutional framework of the European Economic and Monetary Union (EMU). The analysis suggests that monetary union is contingent upon high economic integration and strong political commitment. However, political union is not an ex-ante requirement. Outside factors such as systemic shocks and globalization seem to speed up the pooling of sovereignty in the economic domain. A firm commitment to stability-oriented monetary and fiscal policies is a precondition for gaining credibility and trust within and outside a monetary union. Last, but not least, convergence criteria, fiscal rules and strong institutions are necessary to help ensure and monitor the participants' compliance. However, the European experience is not a blueprint for regional integration that can be directly and entirely applied to other regions.
Keywords: E50; E61; F02; F33; 330; Economic and Monetary Integration; International Monetary Arrangements and Institutions; Monetary Policy and Central Banking; Macroeconomic Policy Formation